Analisis Bahasa Gender dalam Fatwa tentang â€œMusawat Al Marâ€™ah bi Al Rajulâ€ Oleh: Ahmad Al-Shurbasy dalam Kitab â€œYasâ€™alunak fi al-Din wa al-Hayatâ€ - Muhammad Afthon Ulin Nuha (Mu'allim, 2022)
Gender issues are now in the great spotlight in the eyes of the wider community. Gender is generally identified as the difference between men and women from a socio-cultural perspective. Gender in general can be defined as a cultural concept that distinguishes between men and women from a socio-cultural perspective that can change according to changing times. Apart from that, gender issues regarding the roles between men and women in society are based on socio-cultural constructions and the history of society, not solely because of biological, anatomical or sexual aspects. Departing from this problem the author considers it necessary to express thoughts about Gender Language in the Fatwa about the text "Musawat Al Mar'ah bi Al Rajul". By using the library research method, which is then processed using an inductive or deductive approach, it is expected to be able to conclude the Fatwa on Musawat Al Mar'ah bi Al Rajul by Ahmad Al-Shurbasy written in the book Yas'alunak fi al-Din wa al-Hayat, consists of six paragraphs. Each paragraph contains the author's thoughts on the similarities between men and women, as well as the differences between the two (gender) from the perspective of Islam. In this study, it was also found that in expressing his thoughts on gender, he conveyed it using clear, straightforward, and firm language. This kind of language pattern is indeed appropriate to display thoughts about a problem that is problematic. By using such language, it will be able to provide an understanding of gender proportionally.